2008
DOI: 10.1177/0269881108098820
|View full text |Cite
|
Sign up to set email alerts
|

A UK consensus on the administration of aripiprazole for the treatment of mania

Abstract: Aripiprazole has recently received approval for the treatment of moderate to severe manic episodes in bipolar I disorder and prevention of new manic episodes in aripiprazole-responsive patients. Aripiprazole differs from other antipsychotics in its pharmacology, and the need for prescribing guidance in the UK was recently identified. A UK multidisciplinary panel was convened in November 2007. This report describes the consensus agreed during the meeting on the optimal approach to prescribing aripiprazole: how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
(49 reference statements)
0
11
0
1
Order By: Relevance
“…When switching to aripiprazole, the therapeutic dose of current treatment should be maintained while adding aripiprazole 15 (5 to 20) mg/day. Only once an effective dose of aripiprazole is reached should previous medication be reduced [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…When switching to aripiprazole, the therapeutic dose of current treatment should be maintained while adding aripiprazole 15 (5 to 20) mg/day. Only once an effective dose of aripiprazole is reached should previous medication be reduced [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are known CYP2D6 PMs, FDA recommends administration of half of the usual dose of aripiprazole, and the DPWG guidelines recommend reducing maximum daily dose to 10 mg/day or 300 mg/month, i.e., 67-75% of the standard maximum dose. 15 Given that at a dose as low as 2 mg, D 2 receptor occupancy is ∼70% (71.6 ± 5.5%, Kegeles et al, 2008), and the recommendation by consensus guidelines of doses of aripiprazole lower than those used in the initial marketing phase of the drug (Aitchison et al, 2009), it may well be recommendable to start at the lowest dose (2 mg) and to go no higher than 5 mg in CYP2D6 poor metabolizers. While there are as yet no guidelines for other CYP2D6 phenotypic groups, in the case of IMs, the Japanese data would suggest that a cautious dosing in the 2-5 mg range should be appropriate.…”
Section: Aripiprazolementioning
confidence: 99%
“…65 In trials with smaller sample sizes, olanzapine was shown to be equal to lithium in treating mania, 66 placebo-controlled studies comparing olanzapine to divalproex have found no difference between the two, 67 Pharmacological Treatment of Bipolar Disorder 271 and other studies have reported olanzapine to be more efficacious than divalproex. 68,69 Other antipsychotics such as aripiprazole have also been studied and recommended as monotherapy for acute mania 70 and found to comparable in efficacy to haloperidol 71 and lithium. 72 Controlled studies of ziprasidone have reported efficacy in acute mania 73,74 although a recent, placebo-controlled study reported lower efficacy in comparison to haloperidol.…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%